Implementing design tools for military vehicles in an open-source computer-aided engineering framework - Tan, Young Kiat Zenn (2017)
Military vehicle design in the USA has been governed by MIL-STD 1472G, which establishes human factor guidelines for operators in vehicles. However, the guidelines do not account for the distribution of occupant characteristics or the effect of body-borne gear, and the vehicle-design portions of the standard have not been significantly upgraded since the 1980s. UMTRI’s Seated Soldier Study measured soldiers of various stature and garb in a seated driver’s mockup workstation, empirically determining preferred seat and steering wheel settings. Statistical models developed from these data predict the distributions of key body landmarks and adjustable components, including knees, elbows, eyes and seat locations. Application of the results of the Seated Soldier Study to vehicle design requires a computer-aided engineering framework. To eliminate the problems of commercial software licensing and incompatibility between users, this study created an open-source implementation of the Seated Soldier design tool using Python, a widely used open-source object-oriented programming language, and FreeCAD, an open-source computer aided engineering program. The implementation references input files for anthropometric and vehicle data, constructs geometric representations of accommodation models eye location, seat position, helmet clearance and other critical design variables. The input files and Python code are all in human-readable format, facilitating verification and tailoring to specific needs. Vehicle geometry analyses can be conducted in FreeCAD, or the geometry representing the accommodation models can be exported via a variety of file formats, including IGES and STEP, for use in other computer-aided engineering software systems.